The effect of COVID-19 in a newly established burn center - Sabriye Dayı; Selma Beyeç; Şeyhmus Alpağat (Elsevier, 2021)
Objective: This study aims to investigate the effects of COVID-19 on epidemiological features, burn agent, burn percentage, and hospitalization time in a burn center. Methods: This single-center, retrospective study included a total of 401 patients admitted to our study center between October 2019 and July 2020. The patients who were admitted before March 1, 2020, were considered the pre-March group, and those who were admitted after March 1, 2020, were considered the post-March group. According to their age, the patients were further divided into groups as those aged ≤ 18 years and those aged > 18 years. Demographic and clinical characteristics of patients, burn agent, burn surface area, COVID-19 status, and treatment and follow-up data were recorded. Results: Our study results showed no significant difference in the number of patient admission, age, and sex of patients, burn agents and length of hospital stay before and after the COVID-19 outbreak. Conclusions: Burn centers can work safely in COVID-19 outbreak, paying special attention to precautions mandated by the national and global health authorities. However, the increase in pandemic burden may force the burn centers to be converted into alternate COVID-19 facilities. In such cases, the care of burn patients may pose a great problem.